23rd international convention song book (Bladmuziek] = AFSCEM songbook - American Federation of State. Country and municipal Employees (AFSCME) (Washington : AFSCME, 1986)
Deze publicatie bevat volgende liederen
Carry it on
Solidarity Forever
We shall not be moved
Roll the union on
Which side are you on?
Talking union
The mill was made of marble
Hard times in the mill
We are building a strong union
John Henry
Automation
Hold the fort
Union train
You've got to go down and join the union
Joe Hill
Union maid
The soup song
Hallelujeh, I'm a bum
On the line
It could be a wonderfull world
Too old to work
Casey Jones
Pie in the Sky
Study war on work
Free at last
I dreamed of Martin Luther king
Oh freedom
We shall overcome
How did you feel
Come and go with me
This little light of mine
Miner's strawberries
Four day week
When a fellow is out of a job
Desde Delano Voy
That's all
Union man
A dollar ain't a dollar anymore
Magic penny
On our way with AFSCME
This land is your land
Engels
Partituur
Keywords: partituren; liederen